Reference on Thermophysical Properties: Density and Viscosity of Several Gases by Using Macro Excel (RSSDFIUSK vs. 1) - Elin Yusibani (Universitas Syiah Kuala, 2015)
A source code for calculating reference on thermophysical properties: density and viscosity for several gases (nitrogen, helium, hydrogen, argon and air) has been developed under Visual Basic for Applications (VBA) programming in MS Excel (as a macros). Selected density and viscosity equations have been chosen as a basic equation in the VBA programming as a user-defined function. This macro is very useful for engineers and researchers due to enhance their experimental and/or theoretical studies.